Potencial e cinética de adsorção de cromo hexavalente por fibra de coco in natura (Cocos nucifera) : Potential and adsorption kinetics of hexavalent chromium by raw coconut Fiber (Cocos nucifera) - Franguelli, Fernanda Paiva, 1991- (2018)
Orientador: Katia Tannous